AL-HAWIZEH MARSH MONITORING METHOD USING REMOTELYSENSED IMAGES - Muhsin, Israa (Iraqi Journal of Science, 2024)
The main objectives of the present research are of two goals; first, to define andlocale the main cover types (components) of AL-Hawizeh Marshes, and second, totrack and detect the changes encountered in these cover types (components) duringthe last three decades time episodes To fulfill these goals, LANDSAT and MODISimages were applied. The LANDSAT images (MSS-1973, TM-1990 and ETM+2002) were used to determine the Marshlands cover types before, during and afterthe Marsh destruction (marshes dehydrations). One MODIS image was selected tocover the main changes that have been happened in 2010. Programming; Supervisedclassifications (minimum distance classification) were applied for monitoring themean changes that have been happened on the objectives of Al-Hawizeh Marsh.